Exploring Effective Strategies for Fostering Economic Growth in Developing Nations - Raut, Bin Bahadur (International Research Journal of MMC, 2024)
Achieving sustainable economic growth is a critical challenge for developing nations. Economic growth is the increase in the production of goods and services in an economy over a specific period, typically measured by the rise in real gross domestic product (GDP). This article explores effective strategies for fostering economic growth, drawing from existing literature published between 1934 and 2024. Key factors identified include robust governance, infrastructure development, education, and technological innovation. The role of Foreign Direct Investment (FDI) and trade liberalization in stimulating economic activities is emphasized. Inclusive policies targeting poverty reduction and social inequality are crucial to ensure widespread benefits of growth. The article concludes investment in education and skills development, promotion of infrastructure development: promotion of infrastructure development, strengthening institutions and governance: promotion of entrepreneurship and innovation, trade liberalization and regional integration, health and social protection systems, investment in human capital, promoting gender equality, enhancing governance and reducing corruption, supporting small and medium enterprises, encouraging foreign direct investment , fostering innovation and technology adoption, and implementing sound macroeconomic policies as effective strategies for fostering economic growth. The findings highlight the necessity of integrating macroeconomic stability, institutional reforms, and human capital development for sustained economic progress. The study suggests that strategic investments in human capital, strong governance frameworks, and adaptive economic policies can enhance growth prospects, providing valuable insights for policymakers and development practitioners.